(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article considers the concepts of «hypertext» and «hyperlink», the material on which was introduced into the educational-methodological complex of the Russian language for the experimental eleventh grade of the 12-year educationmodel. It analyzes the peculiarities of functioning of texts in the Internet and their forms and gives a brief description of the sites which are most popular among students. The article contains the scientific and methodological commentary on the corrections course that completes the section of the textbook.